The Effect of Islamic Work Ethic and Productivity on Work Quality Through The Employee Performance - Ahmad Hazas Syarif; Afida Rahmawati; Muhammad Iqbal Fasa (Review of Islamic Economics and Finance (RIEF), 2019)
The Islamic work ethic and productivity are parts of the work concept that raise the value of forming a good personality in work based on the principle in Islam. The research investigated 40 employees as research samples through quantitative methods: questionnaire (questionnaire), documentation, and observation. The used analysis included validity test, reliability test, statistical collinearity test, partial test, and determination test (R2). The tool in analyzing the data was pathway analysis with the Smart Pls 3.0 program. The results found that the Islamic Work Ethic has a positive washback on Employee Performance, Work Quality, and Productivity. Employee Performance has a positive washback on employee performance with a positive and significant effect on work quality. Productivity does not significantly influence employee performance, and it also does not significantly influence work quality.